The consequences of urbanization on vegetation photosynthesis in the Yangtze River Delta, China - Yu, Huilin; Zhang, Jie; Kong, Xiangcong; Du, Gege; Meng, Baoping; Li, Meng; Yi, Shuhua (Frontiers in Forests and Global Change, 2022)
Vegetation photosynthesis is a critical component of terrestrial carbon cycles, and its peak value (peak photosynthetic rate) dominates plant CO2 uptake. Urbanization has significantly influenced vegetation photosynthesis by changing environmental conditions directly (replacement of vegetated surfaces with impervious surfaces) and indirectly (e.g., atmospheric and climatic conditions). Although some studies have investigated the effects of urbanization on vegetation productivity across the whole study area, how the peak photosynthetic rate responds to urbanization for different vegetation types has received scant scholarly attention. Here, using the urban-rural gradient approach, we explored the effects of urbanization on the peak photosynthetic rate (surrogated by GPPmax and EVImax) of different vegetation types across urbanization intensity (UI) gradients in the Yangtze River Delta Urban Agglomeration (YRDUA). The results showed that (1) the GPPmax and EVImax of the forest, grassland, and wetland decreased with urban intensity. GPPmax and EVImax in rural areas (UI ≦ 1%) were 36.62 and 30.47% higher than those of urban areas (UI > 1%) overall vegetation types. (2) The indirect impacts can offset or exacerbate the direct loss of vegetation photosynthesis caused by urbanization in YRDUA. Especially for forest ecosystems in YRDUA, the negative direct urbanization effect is exacerbated by the indirect reduction in vegetation growth. However, the indirect effects of urbanization on grassland and wetland offset 47.08 and 87.23% loss of GPPmax, and 34.17 and 79.73% loss of EVImax due to the reduction of vegetated surface area, respectively. (3) The indirect impact of urbanization on vegetation photosynthesis was dominated by the elevated daytime land surface temperature (LSTday). Our study highlights the necessity of distinguishing the various effects of urbanization on vegetation photosynthesis, which may help stakeholders formulate more reasonable urban environmental planning.